Complications of Hardware Removal. (17th November 2021) - Kellam, Patrick J.; Harrast, John; Weinberg, Maxwell; Martin, David F.; Davidson, Nathan P.; Saltzman, Charles L.
Abstract : Background: While hardware removal may improve patient function, the procedure carries risks of unexpected outcomes. Despite being among the most commonly performed orthopaedic procedures, scant attention has been given to its complication profile. Methods: We queried the American Board of Orthopaedic Surgery (ABOS) de-identified database of Part II surgical case lists from 2013 through 2019 for American Medical Association Current Procedural Terminology (CPT) implant-removal codes (20680, 20670, 22850, 22852, 22855, 26320). Hardware removal procedures that were performed without any other concurrent procedure ("HR-only procedures") were examined for associated complications. Results: In the 7 years analyzed, 13, 089 HR-only procedures were performed, representing 2.1% (95% confidence interval [CI], 2.1% to 2.2%) of the total of 609, 150 surgical procedures during that period. A complication was reported to have occurred in association with 1, 256 procedures (9.6% [95% CI, 9.1% to 10.1%]), with surgical complications reported in association with 1, 151 procedures (8.8% [95% CI, 8.3% to 9.3%]) and medical/anesthetic complications reported in association with 196 procedures (1.5% [95% CI, 1.3% to 1.7%]). Wound-healing delay/failure (2.1% [95% CI, 1.8% to 2.3%]) and infection (1.6% [95% CI, 1.4% to 1.8%]) were among the most commonly reported complications after HR-only procedures, but other serious events were reported as well, including unexpected reoperations (2.5% [95% CI, 2.2% to 2.7%]), unexpected readmissions (1.6% [95% CI, 1.4% to 1.8%]), continuing pain (95% CI, 1.2% [1.0% to 1.4%]), nerve injury (0.6% [95% CI, 0.4% to 0.7%]), bone fracture (0.5% [95% CI, 0.4% to 0.6%]), and life-threatening complications (0.4% [95% CI, 0.3% to 0.5%]). Conclusions: Hardware removal is one of the most commonly performed orthopaedic procedures and was associated with an overall complication rate of 9.6% (95% CI, 9.1% to 10.1%) in a cohort of recently trained orthopaedic surgeons in the United States. Although specific complications such as infection, refractures, and nerve damage were reported to have relatively low rates of occurrence, and associated life-threatening complications occurred rarely, surgeons and patients should be aware that hardware removal carries a definite risk. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.